Factors influencing households' participation in recycling - Vicente, P.; Reis, E. (Waste Management and Research, 2008)
The success of a recycling programme depends on the active and sustained participation of citizens in the correct separation and collection of recyclable waste. An effective study of strategies aimed at augmenting people's involvement in recycling involves understanding which factors influence the decision to co-operate with a recycling programme. This research investigates the influence of attitudes, incentives, presence of children in household and information through direct media, on households' participation in recycling. The results suggest that positive attitudes toward recycling and information are important factors in explaining recycling participation. Some guidelines that may be considered in future communication and intervention strategies designed to promote recycling participation are discussed.